Hydrogen–vacancy–dislocation interactions in α-Fe. (23rd December 2016) - Tehranchi, A; Zhang, X; Lu, G; Curtin, W A
Abstract: Atomistic simulations of the interactions between dislocations, hydrogen atoms, and vacancies are studied to assess the viability of a recently proposed mechanism for the formation of nanoscale voids in Fe-based steels in the presence of hydrogen. Quantum-mechanics/molecular-mechanics method calculations confirm molecular statics simulations based on embedded atom method (EAM) potential showing that individual vacancies on the compressive side of an edge dislocation can be transported with the dislocation as it glides. Molecular dynamics simulations based on EAM potential then show, however, that vacancy clusters in the glide plane of an approaching dislocation are annihilated or reduced in size by the creation of a double-jog/climb process that is driven by the huge reduction in energy accompanying vacancy annihilation. The effectiveness of annihilation/reduction processes is not reduced by the presence of hydrogen in the vacancy clusters because typical V–H cluster binding energies are much lower than the vacancy formation energy, except at very high hydrogen content in the cluster. Analysis of a range of configurations indicates that hydrogen plays no special role in stabilizing nanovoids against jog formation processes that shrink voids. Experimental observations of nanovoids on the fracture surfaces of steels must be due to as-yet undetermined processes.